Understanding research in the digital age - Quinton, Sarah; Reynolds, Nina (Sage, 2018)
This is a guide to understanding digital research from both a conceptual and practical perspective, helping the reader to make sense of the issues, challenges, and opportunities of social science research in the digital age.